Active Control of an offshore container crane - Nguyen, Ngo Phong (2019)
Open sea loading/unloading cargo provides a potential solution to minimize problems related with port construction, expansion and congestion. This process involves a crane attached to a mobile harbor which dynamically handle container from a large container anchored in deep water . The control objective during the operation is to keep the payload in the desired position under the presence of ocean waves. This paper presents a robust control strategy for trajectory tracking and sway suppression of an offshore container crane. The asymptotic stability of closed- loop system is guaranteed by a control law derived for the purpose. Experimental results are provided to indicate the efficiency of the proposed control strategy